Sports Orthopedics - Engel T; Arampatzis A; Moreno Català M; Kopinski S; Mayer F (Dynamic Media Sales Verlag, 2018)
Background: This overview provides an introduction to neuromuscular adaptations by exercise interventions based on random perturbations. It is outlined that specific therapeutic intervention based on perturbations may improve spine stability during disturbances as well as neuromuscular control errors and thereby may increase the efficiency of treatment in low back pain.Methods: Specific experimental approaches to assess neuromuscular control of trunk stability during and after perturbations are presented. Further, evidence of neuromuscular adaptations after perturbation-based exercise interventions is given. Finally, a concept to transfer perturbation-based exercises from laboratory conditions to low-back pain therapy settings is introduced.Results and Discussion: Well-established (e.g. quick-release experiments) and novel (e.g. walking perturbations) techniques could indicate neuromuscular deficits in low-back pain compared to asymptomatic controls in response to sudden perturbation experiments applied during quick-release experiments, during perturbed isokinetic strength testing and during sudden stumbling incidents in walking. A novel perturbation training, induced by continuously variable and unpredictable disturbances, successfully served to increase the neural noise in the nervous system. Evidence indicated that neural networks that have been formed in the presence of noise would be more robust and efficient to cope with environmental changes. Finally, the development and evaluation of a perturbation-based training program consisting of core-specific exercises which can be carried out without expensive laboratory perturbation equipment isoutlined. KEY WORDS: MiSpEx, Perturbation Training, Neuromuscular Control, Low Back Pain